2020
DOI: 10.5001/omj.2020.109
|View full text |Cite
|
Sign up to set email alerts
|

Local Usage of Nigella sativa Oil as an Innovative Method to Attenuate Primary Dysmenorrhea: A Randomized Double-blind Clinical Trial

Abstract: Objectives We sought to determine the effect of topical application of Nigella sativa (black seed) oil, on the primary dysmenorrhea intensity. Methods We conducted a randomized, double-blind clinical trial on 124 female students, 18–22 years old, living in the dormitories of Sabzevar Universities. After a primary assessment, participants were randomly divided into two groups. The first group rubbed two drops of N. sativa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The drug formulation and bioavailability of TQ is restricted by its hydrophobic characteristics [ 59 ]. Administration of TQ can occur through several routes, including systemic intraperitoneal, intravenous, oral subacute and sub-chronic administration, besides the localized drug delivery of TQ [ 6 , 60 , 61 ]. In the current investigation the reviewed in vivo studies reported the local periodontal application of 0.1–0.2% TQ gel [ 62 , 63 , 64 ] and similarly in the form of fabricated periodontal chips containing 2.5 mg of TQ [ 65 ].…”
Section: Nigella Sativa and Thymoquinone As Thementioning
confidence: 99%
“…The drug formulation and bioavailability of TQ is restricted by its hydrophobic characteristics [ 59 ]. Administration of TQ can occur through several routes, including systemic intraperitoneal, intravenous, oral subacute and sub-chronic administration, besides the localized drug delivery of TQ [ 6 , 60 , 61 ]. In the current investigation the reviewed in vivo studies reported the local periodontal application of 0.1–0.2% TQ gel [ 62 , 63 , 64 ] and similarly in the form of fabricated periodontal chips containing 2.5 mg of TQ [ 65 ].…”
Section: Nigella Sativa and Thymoquinone As Thementioning
confidence: 99%
“…The volatile oil from Nigella seeds suppressed both spontaneous and oxytocin-induced contractions in the uterine smooth muscle of rats and guinea pigs 7 . N. sativa's analgesic effect has also been clinically demonstrated 8,9 . Except for depression and stomach bloating, Nigella sativa oil was found to diminish the intensity of all Premenstrual syndrome symptoms 10 and Huseini et al verified the analgesic effects of Nigella sativa on patients with cyclic mastalgia 11 .…”
Section: In-vivo Evidence To Relive Primary Dysmenorrhea and Premenst...mentioning
confidence: 99%
“…Female adolescents are populations that expe-rience various changes in hormonal, physical, cognitive and emotional maturity as well as social status in society. [1][2][3][4] This change can be identified from the responsibilities they will face in society and their new roles. 5 Physical changes are anoth-er issue that occurs in the adolescent population.…”
Section: Introductionmentioning
confidence: 99%